2014
DOI: 10.4329/wjr.v6.i3.36
|View full text |Cite
|
Sign up to set email alerts
|

Imaging pitfalls of pancreatic serous cystic neoplasm and its potential mimickers

Abstract: The aim of this article is to clarify diagnostic pitfalls of pancreatic serous cystic neoplasm (SCN) that may result in erroneous characterization. Usual and unusual imaging findings of SCN as well as potential SCN mimickers are presented. The diagnostic key of SCN is to look for a cluster of microcysts (honeycomb pattern), which may not be always found in the center. Fibrosis in SCN may be mistaken for a mural nodule of intraductal papillary mucinous neoplasm (IPMN). The absence of cyst wall enhancement may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The microcystic type demonstrates a cluster of microcysts, the so called “honeycomb pattern” and is associated with a central scar in about 30% of cases [2]. Diagnosis can be difficult as the fibrosis within this subtype may mimic a mural nodule within an IPMN [11]. The oligocystic variant shares features with mucinous cystic neoplasms and branch duct IPMN.…”
Section: Discussionmentioning
confidence: 99%
“…The microcystic type demonstrates a cluster of microcysts, the so called “honeycomb pattern” and is associated with a central scar in about 30% of cases [2]. Diagnosis can be difficult as the fibrosis within this subtype may mimic a mural nodule within an IPMN [11]. The oligocystic variant shares features with mucinous cystic neoplasms and branch duct IPMN.…”
Section: Discussionmentioning
confidence: 99%
“…Pitfalls may arise from several factors: the macro- and oligo-cystic types of SPN can appear similar to pseudocysts or MCN. Rarely the solid form of SPN may be confused with other hypervascular well-circumscribed pancreatic tumors, in particular neuroendocrine tumors and solid pseudopapillary neoplasms[ 18 , 19 , 26 - 28 ]. In contrast to the mentioned reports, an atypical appearance on CT was found in 61.1% of cases in a study of 72 confirmed SPNs[ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…We excluded the nonsurgical cases. To our knowledge, only 19 cases including our case have been published with a pathological confirmation ( Table I ) ( 2 , 3 , 5 , 8 19 ).…”
Section: Discussionmentioning
confidence: 97%